Penentuan Dosis Efektif Ekstrak Daun Pacar (Lawsonia inermis L.) sebagai Antiinflamasi - Selvi Megawati; Herman Herman; Muhammad Amir Masruhim (Journal of Tropical Pharmacy and Chemistry, 2013)
Has been conducted a research of dose determination of effectiveness extract of Lawsonia inermis L. as anti-inflammatory on Rattus norvegicus. The purpose of this research is to gain an in depth understanding of effective dose of Lawsonia inermis L. as anti-inflammatory toward the reduction time of swelling on Rattus norvegicus’ feet .The method which being used was carrageenan induced on Rattus norvegicus’ feet. Rattus norvegicus were devided to 6 (six) group which a group as negative control was given sodium CMC orally, a group as positive control was given Sodium Diclofenac orally, and 4 (four) as test was given extract with 4 doses variation (50mg/kg, 100mg/kg, 150 mg/kg, and 200 mg/kg) orally to each of mice that has pre-conditioned to swell on its foot. The result shows that T-Count is bigger than T-Table with significant standart 0,05 and smaller than T-Table with significant standart 0,01. It proves that there is significant difference between sodium diclofenac and extract of Lawsonia inermis L in 100mg/kgBW. That concludes that extract of Lawsonia inermis L. has anti-inflammatory effect with effective dose as anti-inflammatory in 100mg/kg. Keywords : Lawsonia inermis L., Anti-inflammatory., Rattus norvegicus. Abstrak Telah dilakukan penelitian penentuan dosis efektif ekstrak daun pacar (Lawsonia inermis L.) sebagai antiinflamasi pada tikus putih (Rattus norvegicus). Penelitian ini bertujuan untuk mengetahui dosis ekstrak daun pacar yang efektif sebagai antiinflamasi terhadap waktu penurunan bengkak pada kaki tikus putih. Metode yang digunakan yaitu induksi karagenan pada kaki tikus putih. Tikus putih dikelompokkan menjadi 6 kelompok yaitu kelompok kontrol negatif diberikan natrium CMC, kelompok kontrol positif diberikan natrium diklofenak dan 4 kelompok uji diberikan ekstrak dengan 4 variasi dosis yaitu 50 mg/kg, 100 mg/kg, 150 mg/kg dan 200 mg/kg yang masing-masing diberikan secara oral dan tiap kaki tikus dikondisikan bengkak terlebih dahulu. Hasil penelitian ini membuktikan ekstrak daun pacar memiliki kemampuan sebagai antiinflamasi dengan dosis efektif 100 mg/kgBB. Kata Kunci: Lawsonia inermis L., Antiinflamasi, Rattus norvegicus.